Cozinhas, eletrodomésticos e modos de vida: implicações dos eletrodomésticos nas transformações de rotinas domésticas na cozinha, em residências de Florianópolis/SC - Martins, Conceição Garcia (2013)
The aim of this thesis is to understand how the kitchen environment and the home appliances are articulated to the people´s lifestyle. It assumes that people organize their lives in different ways, anchored in habits and values that were being created, maintained or modified throughout the history of humanity. These habits and values are due to the cultural, social, economic, geographic, political and technological contexts in which people live, as well as the material and immaterial personal background of each one of them, interrelated and interdependent in the composition of the environment, manifesting the complexity and the cultural diversity. The kitchen is seen as an environment of cultural expression and, thus, the expression of identities. It involves not only food preparation and serving, but also the organization of different types of artifacts in this space, as well as the positioning and the kitchen functions in the housing context. These elements represent symbolic values of its residents (or users), in different degrees of interference, because there are those who have more or less influence on this space formation and maintenance. With this perspective in mind, this study is anchored in a theoretical interdisciplinary basis that moves mainly among anthropology, sociology, architecture and design, aiming to clarify issues related to the origins of the kitchen and the social changes associated with the development of technological resources in this environment, especially, to home appliances. Understanding that social changes and technological development constitute integrated product and process in a system, a qualitative and interpretative research with couples from the city of Florianópolis/SC has been conducted. The main goals of this research were: to identify and interpret how the routines are established in the home environment specifically in the kitchen; to identify and interpret how people perceive the interference of technological resources in their daily lives in the home, specifically in the kitchen; to identify and interpret consumption habits of electronic artifacts in the home environment, related to the kitchen; to identify and interpret differences in gender relations in the household, especially in the kitchen, realizing that all this takes place in scenarios and contexts of cultural diversity and hybridization. The survey results enable to broaden and deepen the knowledge on the contexts, profiles and requirements of the people to whom the projetual interrelated activities are made such as architecture and design, among others.